Macrosegmentation and strain hardening stages in copper single crystals under compression; International Journal of Plasticity; Vol. 69 - Lychagin D. V. Dmitry Vasilievich; Tarasov S. Yu. Sergei Yulievich; Chumaevsky A. V. Andrey Valerjevich; Alferova (Alfyorova) E. A. Ekaterina Aleksandrovna (2015, 2015)
Title screen